Iso-Kikuchi syndrome: a rare non-hereditary congenital onycho-dysplasia in a new born - Pillai, Sharadraj; Chandel, Anuragsingh; Kamble, Shubham; Chauhan, Varsha (International Journal of Contemporary Pediatrics, 2025)
Iso Kikuchi syndrome or onychodysplasia is a rare congenital condition characterized by total anonychia or dysplasia of the nails of the index fingers, with underlying bony abnormalities. It is usually benign and rarely associated with other conditions. Despite various hypotheses regarding the pathophysiology, the exact etiology remains unknown. We report a case of a full-term male neonate who presented at birth with bilateral anonychia of the index fingers and dysplastic radial half of the nails on the middle fingers. X rays of the hands showed Y-shaped bifid distal phalanges of the index fingers. Systemic and radiological evaluations were otherwise normal. This case highlights the importance of early recognition of this condition to avoid unnecessary diagnostic work up.